INVESTIGATION OF LAND SUITABILITY FOR DUKU PLANTS AT RASUAN AND UJAN MAS IN SOUTH SUMATERA - Oktaf Juairiyah; Siti Masreah Bernas; Indra Yustian (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Duku becomes a seasonal flagship commodity in South Sumatra. In the process of growth and production of duku, environmental and soil factors are very influential including pH, C-organic, Nitrogen (N), Phosphorus (P) and Potassium (K). The purpose of this study was to find out the suitability class of land for duku plants at two locations of duku plants based on age. The research was conducted by sampling of soil in two locations, namely Rasuan Village of OKU Timur and Ujan Mas of Muara Enim with the grouping of the age of duku plants under 25 years, between 25-49 years, 50-75 years and over 75 years. The results shows that the suitability of land for duku plant in Rasuan Village is more suitable than in Ujan Mas Village. The suitability of land in Rasuan Village is indicated by higher soil pH, C- Organic, N Total, and K values than in Ujan Mas Village. The age of the plant also affects the biological C-Organic and P2O5.